Oral Candidiasis pada Pasien Kanker Paru yang Menjalani Radioterapi: Laporan Kasus - Dilla Adilah Utami; Maulina Triani; Nunky Arum Gayatri; Anindita Laksitasari (Fakultas Kedokteran Gigi Universitas Jember, 2023)
Radiotherapy is one of the modalities of cancer therapy. One of the effects of radiotherapy in the oral cavity is that it can increase the occurrence of opportunistic infections such as oral candidiasis. The purpose of this case report is to describe the oral manifestations that occur in lung cancer patients undergoing radiotherapy. A 52-year-old female patient complained of dry lips and mouth that had been felt since 2 weeks ago. The patient has a history of lung cancer and anemia, the patient is being treated at Prof. Dr. Margono Soekardjo Hospital, the patient has undergone 20 radiotherapy procedures and blood transfusion treatments. Treatment plans that can be given Non-pharmacological therapy in the form of communication, information, and education provided to patients in order to avoid some of the predisposing factors for candidiasis and the need for collaboration with pulmonary specialists who are dealing with systemic diseases. Topical antifungal drug therapy is nystatin oral suspension. Radiotherapy patients are patients with immunocompromised conditions that increase the incidence of infections such as oral candidiasis The principles of management of oral candidiasis include administration of antifungal agents to suppress fungal, identification and correction of predisposing factors and elimination of sources of infection in the oral cavity.